Pointing Hand Stimuli Induce Spatial Compatibility Effects and Effector Priming - Nishimura, Akio; Michimata, Chikashi (Frontiers in Psychology, 2013)
The present study investigated the automatic influence of perceiving a picture that indicates other’s action on one’s own task performance in terms of spatial compatibility and effector priming. Participants pressed left and right buttons with their left and right hands respectively, depending on the color of a central dot target. Preceding the target, a left or right hand stimulus (pointing either to the left or right with the index or little finger) was presented. In Experiment 1, with brief presentation of the pointing hand, a spatial compatibility effect was observed: Responses were faster when the direction of the pointed finger and the response position were spatially congruent than when incongruent. The spatial compatibility effect was larger for the pointing index finger stimulus compared to the pointing little finger stimulus. Experiment 2 employed longer duration of the pointing hand stimuli. In addition to the spatial compatibility effect for the pointing index finger, the effector priming effect was observed: Responses were faster when the anatomical left/right identity of the pointing and response hands matched than when the pointing and response hands differed in left/right identity. The results indicate that with sufficient processing time, both spatial/symbolic and anatomical features of a static body part implying another’s action simultaneously influence different aspects of the perceiver’s own action. Hierarchical coding, according to which an anatomical code is used only when a spatial code is unavailable, may not be applicable if stimuli as well as responses contain anatomical features.